IMPLEMENTASI KONSEP ROUTING PADA SISTEM PENGELOLAAN DATA OBAT DI PUSKESMAS - Permana, Eka; Ningsih, Riska (STMIK Subang, 2023)
This research aims to implement the routing concept in the drug data management system at Community Health Centers (Puskesmas) to enhance efficiency and accuracy in drug distribution. As primary healthcare service centers, Puskesmas require a system that can optimize the drug data management process to provide better healthcare services to the community. The research methodology involves analyzing system requirements, designing a suitable routing concept, and implementing it into the drug data management system at Puskesmas. The routing concept considers various factors such as distance, time, and drug availability to determine the optimal route for drug distribution to different units or rooms within the Puskesmas. The expected outcomes of this research include a positive contribution to the efficiency of drug distribution at Puskesmas, reducing drug handling time, and minimizing the possibility of errors in drug stock management. The implementation of the routing concept in this system is anticipated to provide an effective and efficient solution to drug management at Puskesmas, ultimately improving the quality of healthcare services for the community.